(untitled) (Elmergib Journal of Human Sciences, 2026)
Studying the rhetorical styles of the Holy Qur’an helps uncover its hidden secrets and understand its inimitability. Among these secrets is the inflection of its styles, which the Qur’an has diversified in a wondrous manner and employed with remarkable precision. The entire Qur’an stands at the highest level of eloquence and perfection, whether in passages where such rhetorical styles are explicitly employed or in those where they are absent. These styles are used in accordance with the requirements of each context, for it is a revelation from the All-Wise, the Praiseworthy. Since the purposes of prohibition are subtle and varied, and since the ocean of the Holy Qur’an is filled with pearls and jewels, I was motivated to devote my effort to this aspect. Accordingly, this study examines the various forms of prohibition, especially those that occur with meanings other than their original sense, where context and situational indicators reveal their underlying implications.